Molecular and geochemical constraints on anaerobic ammonium oxidation (anammox) in a riparian zone of the Seine Estuary (France) - Naeher, Sebastian; Huguet, A.; Roose-Amsaleg, C.; Laverman, A.; Fosse, C.; Lehmann, M.; Derenne, S.; Zopfi, J. (Springer Netherlands, 2015)
To expand the limited knowledge about the ecological significance of anaerobic ammonium oxidation (anammox) in continental aquatic and terrestrial ecosystems, we studied community structure, abundance, and activity of anammox bacteria in soils and sediments in the wetland of Trou Deshayes, a riparian zone in the Seine Estuary, France. Combining (i) molecular analyses of the genes coding for anammox bacterial 16S rRNA and the enzyme hydrazine oxidoreductase (hzo), (ii) quantification of unique anammox bacterial membrane lipids (i.e. ladderanes), and, (iii) 15N-isotope label incubation experiments with intertidal sediments and irregularly flooded soils nearby, we demonstrated that anammox bacteria were ubiquitous in the studied wetland ecosystem. In both soils and sediments, detected anammox bacteria were related to Candidatus ‘Brocadia’. 16S rRNA genes were generally lower in the more oxygenated soils, but on the same order of magnitude (107–108 copies g−1 d.w.) as found for other river estuaries, riparian zones and agricultural soils. While the C20-ladderane fatty acid with five cyclobutane moieties (C20-[5]-FA) was found in both sediments and soils, other ladderane species were detected only in the wetland sediments.The observed differential ladderane distribution suggests intra-genus differences in the community composition of anammox bacteria between the sediments and the floodplain soils. While the abundance of anammox bacteria was significantly lower in the soils versus the sediments, the potential anammox rates were similar (≤15 and ≤22 nmol N2 d−1 g−1 w.w. sediment and soil, respectively), suggesting lower cell-specific anammox rates in the sediments. The observed potential rates of anammox were rather low, leaving canonical denitrification as the main fixed N removal pathway in this riparian zone. The relative contribution of anammox to the total N2 production (between 3 and 8 %) was similar at all sites, highlighting the dependence of the anammox process on nitrite supply from denitrification across environmental boundaries. Due to this coupling, the dependence of organotrophic denitrification on the quality and stoichiometry of OM also seems to affect the anammox bacterial community. Our results suggest that N removal and mitigation of N supply from agriculture in wetlands by anammox is limited, and much less important than denitrification.